A Contrastive Analysis Study Between English and Macassarese in Request Sentence - Sulastri Sulastri; Rizkariani Sulaiman (Universitas Negeri Makassar, 2020)
This study examines the English and Makassar language request phrases. The imperative phrase of both languages from its form, purpose, and category in a sentence was studied in this analysis. The research used descriptive approach and contrastive analysis in terms of methods, the entire data were gathered by observing and interviewing the native speakers of Lakiung dialects who still speak in their everyday communication. In the analysis, the writer outlined and compared the differences and similarities in request sentences, classified and explained request sentences into subject, predicate, object and adverb. The results revealed that the request sentences in English and Macassarese have some similarities and differences were found in form of sentences and the function of adverb. The differences between English and Macassarese request sentence pattern, particularly on the element of predicate (P) in a sentence. While the similarity was S – P – O – K and S – P construction.